Knowledge of Ghanaian Graduating Undergraduate Nurses About Ageing - Confidence Alorse Atakro MN (SAGE Publishing, 2021)
Introduction Knowledge on ageing has an impact on the quality of care provided to older people. Although older Ghanaians provide various forms of support to family and communities, many of them experience poor nursing care in the Ghanaian health system. There is, however, dearth of evidence regarding knowledge of ageing among Ghanaian nurses. Objective This study therefore used a descriptive survey approach to investigate knowledge of graduating undergraduate nurses on physiological, and psychosocial changes in ageing. Methods Seventy graduating undergraduate nurses were surveyed to identify their knowledge on physiological and psychosocial changes leading to care needs of older people in Ghana. Three undergraduate nursing programs with gerontological nursing courses were purposively selected for the study. Descriptive statistics were used to analyze the data in order to present quantitative descriptions of variables in this study. Results The response rate in the study was 42%. Findings of the study show graduating undergraduate nursing students have inadequate knowledge on ageing. Several gaps in knowledge regarding ageing were identified. Although undergraduate nursing schools had gerontological nursing courses in their programs, over 90% of participating graduating nursing students indicated pain, anxiety and depression are normal aspects in the ageing process. Conclusion It is imperative to improve the current curricula content on gerontological nursing in Ghanaian nursing schools to equip nurses with knowledge and skills needed to provide quality healthcare to older people in Ghana. Improving knowledge on ageing through evidence-informed gerontological nursing curricula content will lead to better nursing care of older Ghanaians. Providing educational opportunities for improved quality nursing care of older Ghanaians is in line with the United Nations (UN) Sustainable Development Goal 3, which aims at providing equal and quality healthcare to all age groups by 2030.